Methods to determine reimbursement rates for diagnosis related groups (DRG): a comparison of nine European countries - Schreyögg, Jonas; Stargardt, Tom; Tiemann, Oliver; Busse, Reinhard (Health care management science, 2006)
Over the past 20 years, most European countries have introduced DRGs or similar grouping systems as instruments for hospital reimbursement. This paper compares and analyzes the methods used to determine prices for inpatient care within DRGs or similar grouping systems employed in nine EU member states (i.e., Denmark, France, Germany, Hungary, Italy, Tthe Netherlands, Poland, Spain and England). It categorizes the systems of patient classification used in these nine countries and compares them according to the three steps necessary in order to set prices: 1.) definition of a data sample, 2.) use of trimming methods and plausibility checks and 3.) definition of prices. It concludes with a discussion on the typical development path of DRG systems and the role of additional reimbursement components in this context.